Passivation/precipitation mechanisms of Al-Cr-Fe Complex Metallic Alloys in acidic chloride containing electrolyte. (10th October 2015) - Beni, A.; Ott, N.; Caporali, S.; Guseva, O.; Schmutz, P.
Abstract: The transition from corrosion product formation to protective passivation has been studied for several Al-Cr-Fe Complex Metallic Alloys (CMA) phases during long immersion time (269 days) in 0.01 mol L −1 HCl + 1 M NaCl at pH 2.0, using ICPMS (Inductively Coupled Plasma Mass Spectrometry) and UV- Visible spectroscopy analysis. The different dissolution mechanisms of the investigated phases could be identified by the formation of either Fe(II) or Fe(III) species. In the case of the actively corroding 12.5%at Cr containing phase, Fe(II) complexes were detected in solution, whereas for the passive 27.2%at Cr gamma phase, Fe(III) species were mainly present due to the passive dissolution of the nm-thick protective oxyhydroxide film. Subsequent Raman characterisations of the surface indicated the presence of a Fe3 O4 -type layer on the corroding low Cr containing phases surface which is in agreement with the formation of a Fe(II)/Fe(III) mixed oxide. Speciation simulations allowed predicting Fe(III)-Cl complexes as stable species in the studied environments and related precipitation phenomena controlling the pH evolution. These results can further be used to characterise the active to passive corrosion transition occurring also in different Fe, Cr- containing alloys (like stainless steels) in acidic domain.